Exenatide once weekly: clinical outcomes and patient satisfaction - Biju Jose1; Abd A Tahrani; Milan K Piya; et al (Patient Preference and Adherence, 2010)
Biju Jose1, Abd A Tahrani1,2, Milan K Piya1,2, Anthony H Barnett1,21Department of Diabetes and Endocrinology, Heart of England NHS Foundation Trust, Birmingham, UK; 2School of Clinical and Experimental Medicine, University of Birmingham, Birmingham, UKBackground: Type 2 diabetes mellitus (T2DM) is a complex disorder in which interactions between environmental and genetic factors result in the development of insulin resistance (in most cases) and progressive pancreatic β-cell failure. The currently available oral anti-diabetes treatments are effective as monotherapy; however, due to the progressive decline in β-cell function, most patients will require the use of combination therapy and eventually insulin to reach glycemic targets. These therapeutic options are not without undesirable side effects such as weight gain and hypoglycemia. Furthermore, T2DM is associated with impaired quality of life (QOL) and poor compliance with treatment. Hence, there is a need for anti-diabetes agents that result in sustained improvements in glycemic control without hypoglycemia or weight gain and have a positive impact on patients QOL and thereby hopefully improve compliance. Incretin-based therapy is the latest addition to anti-diabetes treatments which addresses some of the shortcomings of older treatments.Aims: To review the evidence for the use of exenatide once-weekly.Methods: We have searched Medline using the terms “exenatide”, “exenatide once-weekly”, and “exenatide LA”.Results: Exenatide once-weekly is an incretin mimetic that is currently undergoing phase 3 clinical trials, and has been shown to improve glycemic parameters (HbA1c and fasting and postprandial glucose levels), with low risk of hypoglycemia, causes weight loss, and use was associated with improvements in patient satisfaction which might have a positive impact on treatment compliance.Conclusions: Exenatide once-weekly is effective, well tolerated in patients with T2DM and should be a useful addition to the available range of anti-diabetes treatments.Keywords: diabetes mellitus, incretins, exenatide once-weekly, quality of life, treatment satisfaction